1994
DOI: 10.1002/jcp.1041600215
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal regulation of some steps of thyroglobulin synthesis and secretion in bicameral cell culture

Abstract: Porcine thyroid cells were cultured for 15 days on porous bottom chambers with or without different mixtures of hormones added to serum-free basal medium. Assays with 10% serum were also performed for comparison with previously published results. The effects of the hormones, particularly insulin, TSH and hydrocortisone, were studied on total RNA content, thyroglobulin mRNA level, the amount of thyroglobulin secreted into the apical medium and on glycosylation. Insulin and TSH similarly increased the total RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2000
2000

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…TSH and iodide were also found to regulate the cytosolic volumes and the total amount of proteins without affecting the number of cells. In the absence of iodide, the absolute cytosolic volume increased, but its proportion vs. the total cell volume decreased, showing an increase in the protein content when TSH stimulation was applied alone, partly by increasing the endoplasmic reticulum and the intracellular organelles (10,31). In the absence of TSH but with iodide, the decrease in protein content was associated with an increase in the absolute cytosolic volume and its proportion vs. the total cell volume.…”
Section: Discussionmentioning
confidence: 99%
“…TSH and iodide were also found to regulate the cytosolic volumes and the total amount of proteins without affecting the number of cells. In the absence of iodide, the absolute cytosolic volume increased, but its proportion vs. the total cell volume decreased, showing an increase in the protein content when TSH stimulation was applied alone, partly by increasing the endoplasmic reticulum and the intracellular organelles (10,31). In the absence of TSH but with iodide, the decrease in protein content was associated with an increase in the absolute cytosolic volume and its proportion vs. the total cell volume.…”
Section: Discussionmentioning
confidence: 99%
“…Over many years, we have accumulated extensive data on this culture system, which simulates thyroid metabolism in vivo, up to the stage of secretion of thyroid hormones into the basal medium (unpublished results). We have shown that TSH controlled all the steps of thyroglobulin metabolism that we have studied: thyroglobulin expression and secretion (25)(26)(27)(28), and two post-translational modifications, glycosylation (29,30) and iodination (31).…”
Section: Introductionmentioning
confidence: 99%